Survival Strategy of Randai Sabai Nan Aluih in Nagari Aia Angek, X Koto District, Tanah Datar Regency - Herman, Muthia Chaerani; Bustami, Abd Latif; Perguna, Luhung Achmad (Humanities Horizon, 2024)
Randai is a combination of dance, music, dialogue and theater which depicts social life and stories in Minangkabau society. In facing challenges, it is important to continue to develop relevant and innovative strategies to keep Randai arts alive and thriving in the modern era. This research has two formulations of the problem, namely, first, why has Randai Sabai Nan Aluih survived to this day in Nagari Aia Angek? What is the strategy used by Randai Sabai Nan Aluih to maintain its existence? This study uses a qualitative approach with a descriptive type and applies the social construction theory of Peter L. Berger and Thomas Lukmann. The results of this study reveal that Randai Sabai Nan Aluih managed to survive in Nagari Aia Angek by going through many social processes. To be able to survive Randai Sabai Nan Aluih uses several strategies including adding economic value to Randai Sabai Nan Aluih, maintaining traditional concepts, innovating several parts of Randai such as: updating comedic musical accompaniment, setting up an interesting stage, joining Parinsau studio to strengthen its position Randai as well as making Randai an extracurricular at a school in the village of Aia Angek.